HUKUM DAN ETIKA BISNIS DALAM PRAKTIK PERDAGANGAN MODERN DI INDONESIA - Reka Ruslan; Moch. Givan Andra Pratama; Muh. Reza Zulfikar; Sutrisno Syarifuddin (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2026)
Business law and ethics are two essential elements in conducting economic activities in the modern era. Law serves as a normative framework governing the relationships between businesses, consumers, andthe state, while business ethics serve as moral standards that determine whether business conduct is right or wrong. In practice, various business violations such as breach of contract, fraud, unfair competition, monopolies, labor exploitation, and violations of consumer rights demonstrate that compliance with the law alone is insufficient without ethical awareness. This study aims to analyze the relationship between law and business ethics in modern trade practices in Indonesia, as well as to examine the urgency of applying ethical principles in creating a healthy and just business climate. The research method used is normative legal research with a legislative approach and a conceptual approach. The results of the study indicate that law and business ethics have a complementary relationship. Law provides coercive sanctions, while ethics shapes the moral consciousness of business actors to conduct business honestly, fairly, and responsibly. Therefore, the integration of law and business ethics is essential to realize sustainable trade practices oriented toward social justice.